Ureterocolic Fistula Secondary to Diverticulitis of the Sigmoid Colon after Laparoscopic Salpingo-Oophorectomy: A Case Report and Literature Review - Yamanaka, Hirohumi (Case Rep Obstet Gynecol, 2019)
Ureterocolic fistula is a rare phenomenon and cases secondary to diverticulitis are even rarer. We present a case of ureterocolic fistula secondary to diverticulitis of the sigmoid colon following laparoscopic salpingo-oophorectomy due to endometriomas. To our knowledge, this is the first case that occurred in a patient with gynecologic surgery.